Urgensi Pembentukan Peraturan Desa tentang Pengelolaan Pasar Tuah Benua Desa Sepaso Kabupaten Kutai Timur - Kiki Rustyanti; Rahmawati Al Hidayah; Alfian Alfian (Majelis: Jurnal Hukum Indonesia, 2025)
This research discusses the urgency of establishing a Village Regulation regarding the management of Tuah Benua Market to identify legal issues and the urgency of forming a village regulation. Minister of Home Affairs Regulation Number 42 of 2007 concerning Village Market Management does not specifically regulate market fees, sanctions, and prohibitions on trading outside Tuah Benua Market, resulting in a legal vacuum. This research uses empirical legal methods with direct observation and interviews in the field. The research results are expected to provide recommendations for the formation of effective Village Regulations in the management of Village Markets and support local economic development. The formation of a Village Regulation on the management of Tuah Benua Market is crucial to create legal certainty and improve the management of the Village Market. Village Regulations can regulate prohibitions on trading outside the market area, sanctions for traders who violate, and market fee policies. Thus, Tuah Benua Market can become a orderly, conducive, and beneficial trading center for the surrounding community. Village Regulations must be made considering the needs of the village community and implemented effectively to create a conducive and fair trading environment.